Migration histories of the medieval Afroeurasian transition zone (Leiden ; Boston)
xiii, 478 sayfa
Keywords: “The transition zone between Africa, Asia and Europe was the most important intersection of human mobility in the medieval period. The present volume for the first time systematically covers migration histories of the regions between the Mediterranean and Central Asia and between Eastern Europe and the Indian Ocean in the centuries from Late Antiquity up to the early modern era. Within this framework, specialists from Byzantine, Islamic, Medieval and African history provide detailed analyses of specific regions and groups of migrants, both elites and non-elites as well as voluntary and involuntary. Thereby, also current debates of migration studies are enriched with a new dimension of deep historical time.“ --